Teaching the violent past : history education and reconciliation - Cole, Elizabeth A.; Carnegie Council on Ethics & International Affairs (Lanham : Rowman & Littlefield Publishers : In cooperation with the Carnegie Council for Ethics in International Affairs, 2007)
During an armed conflict or period of gross human rights violations, the first priority is a cessation of violence. For the cease-fire to be more than a lull in hostilities and atrocities, however, it must be accompanied by a plan for political transition and social reconstruction. Essential to this long-term reconciliation process is education reform that teaches future generations information repressed under dictatorial regimes and offers new representations of former enemies. In Teaching the Violent Past, Cole has gathered nine case studies exploring the use of history education to promote.
Introduction: reconciliation and history education / Elizabeth A. Cole -- As generations pass: the challenges of long-term reconciliation in history textbooks -- The trajectory of reconciliation through history education in postunification Germany / Julian Dierkes -- Advancing or obstructing reconciliation? Changes in history education and disputes over history textbooks in Japan / Takashi Yoshida -- Representations of aboriginal people in English Canadian history textbooks: toward reconcilation / Penney Clark -- Reconciliation in process -- History teaching and reconciliation in Northern Ireland / Alison Kitson -- The Spanish civil war and Franco dictatorship: the challenges of representing a conflictive past in secondary schools / Rafael Valls -- Historical memory and the limits of peace education: examining Guatemala's memory of silence and the politics of curriculum design / Elizabeth Oglesby -- Reconciliation jeopardized, undone or not yet attained: aspirational and counter-reconciliatory cases -- History and myth in the Soviet Empire and the Russian Republic / Thomas Sherlock -- On the use and abuse of of Korea's past : an inquiry into history teaching and reconciliation / Roland Bleiker -- The role of history textbooks in shaping collective identities in India and Pakistan / Thomas Sherlock and Jon Dorschner -- Afterward / Audrey Chapman -- Contributors.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Peace -- Study and teaching -- Case studies; Conflict management -- Case studies; Paix -- Étude et enseignement -- Études de cas; Gestion des conflits -- Études de cas; SOCIAL SCIENCE -- General; Conflict management; Peace -- Study and teaching; Geschichtsunterricht; Friedenserziehung; Konflikt; Versöhnung; Peace -- Study and teaching -- Case studies; Conflict management -- Case studies; Konflikt (Motiv); Case studies; Case studies; Études de cas